Avaliação do Potencial do Uso Educacional da Gleba Manga do Céu - Russ, Bruna Ribas (2012)
Igatu, district of Andaraí, is located 410 km from the city of Salvador, has about 390 residents, distributed in 121 families, mostly poor. Children, adolescents and young adults are at social risk, the early pregnancy, alcoholism and family violence are symptoms common. Since 2006 the community of Igatu has been mobilizing througt the organization Centro Cultural Chic Chic, in order to consider this reality, by promoting actions in favor of quality of life of the residents. The Urban Park Igatu (PUI), enacted in may 2007 is a result of this actions. Searching for the miner assets valuation and the PUI, as educational space, this research aims to understand the transformations of Manga do Céu over time, using them to characterize their educational potential. The environmental history and oral history were methodological steps that resulta in two models; the first with the spatialization of areas mined of the Manga do Céu and with patrimonial points; the second in a comics format, with seek to represent the area before mining (1800), during (1950) and later (2012). Guided tours, the questionnaire with high school students, and procedures for classification en reclassification of the database, were steps for modeling the educational potential of the Manga do Céu. The research produced as a final result a model with the areas of greatest educational potential, which coincides with the sectors of the Labyrinth and the Verruga; used by the community for rock climbing. Moreover, others theoretical models were also developed, considering other aspects does not inventoried in this study (geological and biological diversity), in order to extend service to students and stimulate further study. These models subsidize the management of use of the PUI, at the same time, they help teacher in search of using the Manga do Céu as educational space.